Creating Shared Norms in Schools — A Theoretical Approach. Issue 1 (12th April 2016) - Macdonald, Maryanne; Gringart, Eyal; Gray, Jan
Abstract : Whilst some improvements to Indigenous education outcomes have occurred in recent years, there remains considerable inequity in the educational experiences and long-term engagement of Indigenous and non-Indigenous students. One of the factors contributing to the challenging environment for Indigenous students is dissonance of social norms, as a result of ethnic and socioeconomic differences between teacher and student. Many hegemonic culture teachers are unaware of Standpoint Theory and the way in which normative beliefs impact on classroom interactions and student outcomes at the cultural interface. This paper draws on the Theory of Planned Behaviour (TBP) to illustrate ways in which schools can identify areas of ethnic and socioeconomic prejudice impacting classroom interactions, and create shared social norms so that Indigenous students are most likely to experience positive educational engagement. Self-Determination Theory (SDT) is then applied to discuss the type of classroom environment that best enables students to internalise positive educational behaviours in an autonomous manner. Such internalisation is necessary to improve long-term outcomes and postschool educational engagement for Indigenous Australians. The theories explored indicate that motivation for behavioural change relies on the individual's self-perceptions of competence, autonomy and normative beliefs regarding the value of education, and that integration of new behaviours requires an emotionally supportive environment and provision of a meaningful rationale. This paper argues that good practice in Indigenous schooling will address these areas specifically.